THE EFFECT OF TRADITIONAL JUMP ROPE GAME ON IMPROVING GROSS MOTOR SKILLS OF GRADE II STUDENTS OF SDN 54 BANDA ACEH - Is, Zulheri; Subhananto, Aprian (Sport Pedagogy Journal, 2025)
This study aims to evaluate the effect of the traditional game of jumping rope on the improvement of gross motor skills of 7-year-old students. Using a pretest-postes experimental design, 30 students at SDN 54 Banda Aceh were measured through long jump tests, 30-meter runs, and balance before and after the intervention. The results of the pretest showed an average long jump of 1.20 meters, a running time of 30 meters of 9.00 seconds, and a balance time of 11.40 seconds. After participating in the jump rope game program, the results of the postes showed a significant improvement, with the average long jump increasing to 1.60 meters, the running time decreasing to 7.20 seconds, and the balance time increasing to 18.80 seconds. The analysis using the t-test for paired samples showed a p-value smaller than 0.05 for all aspects, which showed a significant difference between the pretest and postes results. These findings confirm that the traditional jump rope game program is effective in improving students' gross motor skills, which are important for children's physical development and health. In addition, this study underscores the importance of integrating physical activity in the physical education curriculum to support the holistic development of students. Thus, traditional games can be adopted as an effective strategy to improve children's physical fitness and motor skills in school. This research contributes to the understanding of effective teaching methods in physical education as well as the importance of physical activity in children's daily lives.Keywords: Traditional Games, Jump Rope, Gross Motor